Exploring Factors Influencing College Females’ Perceptions of Menstruation: A Study on Awareness and Cultural Influences - Nyaupane, Prativa; Thapa, Sonu (NPRC Journal of Multidisciplinary Research, 2024)
This study surveyed 225 respondents on their attitudes towards menstruation, revealing predominantly negative feelings. A significant majority (84.9%) expressed disagreement with feeling proud during menstruation, while none agreed or felt happy about having their period. Most respondents (66.7%) also did not feel excited about menstruating. Similarly, a large portion of respondents (82.2%) were not eager to experience their first period, and 65.8% reported not being happy when they found out about menstruation. Although many respondents disagreed with feeling different during their period, nearly 58.7% agreed that menstruation makes them uncomfortable. When asked if it was acceptable to miss college due to menstrual cramps, 45.3% strongly agreed, indicating that many find menstruation physically challenging. The majority (75.1%) also disagreed with feeling scared, suggesting awareness and understanding of the menstrual process. Respondents were generally open to discussing menstruation, with 72% feeling comfortable talking to friends. However, 62.2% expressed feeling nervous when the word “period” is mentioned. Social stigma remains an issue, as 60.9% disagreed with fearing boys finding out about their period, but a smaller group (24.9%) expressed fear. Finally, 86.2% disagreed that girls should worry during their period. Overall, this survey highlights the widespread discomfort, negative associations, and stigma surrounding menstruation, with respondents showing minimal positive feelings or eagerness towards their periods.